Long-term amelioration of acidity accelerates decomposition in headwater streams. - Jenkins,GB; Woodward,G; Hildrew,AG (Glob Chang Biol, 2013)
The secondary production of culturally acidified streams is low, with a few species of generalist detritivores dominating invertebrate assemblages, while decomposition processes are impaired. In a series of lowland headwater streams in southern England, we measured the rate of cellulolytic decomposition and compared it with values measured three decades ago, when anthropogenic acidification was at its peak. We hypothesized that, if acidity has indeed ameliorated, the rate of decomposition will have accelerated, thus potentially supporting greater secondary production and the longer food chains that have been observed in some well-studied recovering freshwater systems. We used cellulose Shirley test cloth as a standardized bioassay to measure the rate of cellulolytic decomposition, via loss in tensile strength, for 31 streams in the Ashdown Forest over 7 days in summer 2011 and 49 days in winter 2012. We compared this with data from an otherwise identical study conducted in 1978 and 1979. In a secondary study, we determined whether decomposition followed a linear or logarithmic decay and, as Shirley cloth is no longer available, we tested an alternative in the form of readily available calico. Overall mean pH had increased markedly over the 32 years between the studies (from 6.0 to 6.7). In both the previous and contemporary studies, the relationship between decomposition and pH was strongest in winter, when pH reaches a seasonal minimum. As in the late 1970s, there was no relationship in 2011/2012 between pH and decay rate in summer. As postulated, decomposition in winter was significantly faster in 2011/2012 than in 1978/1979, with an average increase in decay rate of 18.1%. Recovery from acidification, due to decreased acidifying emissions and deposition, has led to an increase in the rate of cellulolytic decomposition. This response in a critical ecosystem process offers a potential explanation of one aspect of the limited biological recovery that has been observ